Aetiology, outcomes, and in-hospital mortality predictors of suspected paediatric central nervous system infections in southwestern Uganda: a prospective cohort study - Phuthumani Mlotshwa; Elias Kumbakumba; Dan Nyehangane; Reza Rast; Richard Migisha; Milly Nassejje; Deborah Nanjebe; Yap Boum II; Juliet Mwanga-Amumpaire; Tobias Alfvén; Giulia Gaudenzi (The Lancet Regional Health–Africa, 2026)
Background: Central nervous system (CNS) infections remain a major cause of paediatric morbidity and mortality in sub-Saharan Africa. We aimed to describe the aetiology and outcomes of paediatric CNS infections in southwestern Uganda and identify predictors of in-hospital mortality. Methods: Children aged 0–12 years with suspected CNS infections were recruited upon admission and followed until discharge, transfer, or death between January 2019 and September 2020 at two major hospitals in southwestern Uganda. Blood and cerebrospinal fluid (CSF) underwent routine diagnostics and BioFire FilmArray ME Panel testing. We used modified Poisson regression with robust variance to identify predictors of in-hospital mortality. Findings: Among the 212 children enrolled, in-hospital mortality was 15% (95% CI: 11–20%), while 18% (95% CI:13–23%) were discharged with neurological sequelae. At admission, delayed capillary refill (adjusted risk ratio[aRR] = 5.9; 95% CI: 1.8–20), symptomatic anaemia (aRR = 2.7; 95% CI: 1.1–7.0), and elevated peripheral white blood cell count (aRR = 3.3; 95% CI: 1.8–6.1) were independently predictive of fatal outcomes. Plasmodium species were detected in 20% (n = 42) of cases, and HHV-6 in 9% (n = 19), including instances of co-infection. Among bacterial pathogens in CSF, Streptococcus pneumoniae (11/24) was the most frequently identified, followed by Haemophilus influenzae (4/24) and Neisseria meningitidis (4/24). Interpretation: Despite advances in infectious disease control, children with suspected CNS infections in south western Uganda continue to experience high mortality and neurological sequelae. Strengthened prevention, rapid diagnostics, and simple bedside markers such as delayed capillary refill, symptomatic anaemia, and elevated WBC count could enable earlier risk stratification and improved outcomes in low-resource settings.
Keywords: Central nervous system infections; Meningitis; Aetiology; Paediatrics; Hospital mortality; Low-resource settings